2016
DOI: 10.3402/jchimp.v6.32031
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate use of commercial Antinuclear Antibody Testing in a community-based US hospital: a retrospective study

Abstract: Healthcare providers use antinuclear antibodies (ANAs) to screen and diagnose patients with autoimmune diseases. In the recent years, commercial multiplex ANA kits have emerged as a convenient and fast diagnostic method. Diagnostic testing should follow sequenced algorithms: initial screen followed by specific antibody analysis. Second-level testing as an initial screen for autoimmune disease is inappropriate. We reviewed 68 patients with ANA comprehensive panels over a 6-month period from May 2015 to October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with previous studies showing that ANA testing is pervasive in rheumatology practice. 22,23,27,28,[30][31][32] We observed similar frequencies of ANA positivity in our sample and similarly identified that family physicians order the majority of ANA tests. 27,31 Although there are far more family physicians than other specialists, it has been suggested that family physicians have limited expertise in interpreting ANA tests and may ignore results.…”
Section: Open Researchsupporting
confidence: 75%
“…Our findings are consistent with previous studies showing that ANA testing is pervasive in rheumatology practice. 22,23,27,28,[30][31][32] We observed similar frequencies of ANA positivity in our sample and similarly identified that family physicians order the majority of ANA tests. 27,31 Although there are far more family physicians than other specialists, it has been suggested that family physicians have limited expertise in interpreting ANA tests and may ignore results.…”
Section: Open Researchsupporting
confidence: 75%
“…Multiplex immunoassays have led to a paradigm shift in ANA testing for autoimmune diseases ( 63 ). Rapid throughput techniques have replaced traditional methods like IFA and ELISA in many clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The test names such as “ANA Direct” and “ANA Screen” are confusing misnomers as these tests are not actually measuring the ANA itself. When unexpected results are reported (Case 3), there is uncertainty in interpreting the test report often precipitating referral for rheumatology consultation plus additional testing ( 63 ). ANA determination using a two-step sequential process would be recommended for patients undergoing evaluation for SLE (Case 2).…”
Section: Discussionmentioning
confidence: 99%